Preliminary study of the demo plasma separator - Yegorov, A.M.; Yuferov, V.B.; Shariy, S.V.; Seroshtanov, V.A.; Druy, O.S.; Yegorenkov, V.V.; Ribas, E.V.; Khizhnyak, S.N.; Vinnikov, D.V. (Вопросы атомной науки и техники, 2009)
This paper outlines the preliminary study of a plasma components electromagnetic separator. This device is intended for separating the heavy components of spent nuclear fuel (SNF) from the light ones. The power consumed in this process is expected to comprise about 1·10³ eV per particle. We performed our experiments with the SNF simulating gas mixture. The results obtained permit to draw a conclusion that the effect of separation may be achieved. Описано попередні дослідження можливості розділення важкої та легкої компонент відпрацьованого ядерного палива (ВЯП) при енерговитратах на рівні біля 1⋅10³ еВ/атом на електромагнітному плазмовому сепараторі елементів. Експерименти проводились на суміші газів, що імітує ВЯП. Отримані результати дозволяють зробити висновок про досягнення ефекту розділення. Описаны предварительные исследования возможности разделения тяжелой и легкой компонент отработанного ядерного топлива (ОЯТ) при энергозатратах на уровне около 1⋅ 10³ эВ/атом на электромагнитном плазменном сепараторе элементов. Эксперименты проводились на смеси газов, имитирующих ОЯТ. Полученные результаты позволяют сделать вывод о достижении эффекта разделения.